The association between lipid accumulation product and osteoporosis in American adults: analysis from NHANES dataset - Huawen Pan; Huawen Pan; Xiao Long; Ping Wu; Yongchun Xiao; Huanran Liao; Li Wan; Jianxian Luo; Jianxian Luo; Zhisheng Ji (Frontiers in Medicine)
BackgroundThe Lipid Accumulation Product (LAP), a novel indicator of fat accumulation, reflects the distribution and metabolic status of body fat. This study aims to evaluate the relationship between adult Americans’ prevalence of osteoporosis and LAP.MethodsThis study used data from the NHANES cycles 2007–2010, 2013–2014, and 2017–2018, including 4,200 adults aged 50 and above. LAP was calculated using waist circumference and triglyceride levels, whereas osteoporosis was identified using information from dual-energy X-ray absorptiometry (DXA) assessments of bone mineral density (BMD). Restricted cubic spline (RCS) analysis was evaluated the relationship between LAP and osteoporosis. Additionally, subgroup analyses were conducted to assess the impact of demographic characteristics and health status on the relationship between LAP and osteoporosis.ResultsLAP and osteoporosis were shown to be significantly inversely correlated in the study. In the unadjusted model, the prevalence of osteoporosis and Log LAP showed a significant negative connection (OR = 0.62, 95% CI = 0.52–0.74). Osteoporosis prevalence decreased by 45% in the fully adjusted model for every unit rise in Log LAP (OR = 0.54, 95% CI = 0.44–0.66). RCS analysis revealed a nonlinear association between LAP and osteoporosis prevalence (P-non-linear = 0.0025), showing an L-shaped negative correlation. Subgroup studies showed that, regardless of age, sex, ethnicity, or health condition, there was a constant negative connection between LAP and osteoporosis.ConclusionAccording to this study, there is a substantial negative relationship between adult prevalence of osteoporosis in America and LAP. LAP is an easy-to-use and practical indication that may be very helpful in osteoporosis prevention and early detection.